The Results of War Are Never Final?: Meditations on an American Defeat. Issue 5 (29th July 2021) - Toprani, Anand; Murray, Nicholas; Dennis, Michael
Abstract : Should a Sino-American War start, how will the US deal with the inevitable military setbacks? Most importantly, what would happen if the US loses not simply a battle, but rather a series of engagements culminating in an unmistakable defeat that results in unfavourable peace terms? The US may not like thinking about losing, but considering China's growing capabilities, it can no longer assume victory. Anand Toprani, Nicholas Murray and Michael Dennis argue that, if the US thinks about the consequences of war, and cooperating and working together as a country, it can avoid a conflict with China, and recover more quickly and equitably if it does fight and lose. ◼